Agro-Logistics for Nutmeg and Cocoa Exports from Grenada : A Logistics Chain Approach - Fries, Gwyneth (World Bank, Washington, DC, 2014)
This study is designed to build a link between the study and improvement of agriculture and that of logistics for agricultural exports, and complements the Grenada Small Farmer Vulnerability Reduction project. The objective of logistics chain analysis (LCA) is to understand product movement for two of Grenada's primary agricultural exports and identify opportunities to enhance competitiveness for these and other products by improving logistics. Logistics refers to the infrastructure, machinery, related services, and information systems that allow products to move from the original point of production to the final point of consumption. The analysis identifies where logistics inefficiencies, from the farm gate to the port of exit, increase logistics expenses, travel times, and uncertainty. A strategic plan to increase agricultural exports must involve coordinated public and private investments in the infrastructure, equipment and services necessary for exporters to load and unload products at their own warehouses. Further diagnostic work will be needed to identify the proper technical projects and investments, assess their potential costs and impacts for nutmeg and cocoa exports, as well as for agricultural exports in general.